Estimating the Variance of Wages in the Presence of Selection and Unobserved Heterogeneity - Chen, Stacey H (The Review of Economics and Statistics, 2009)
February 01 2009 Estimating the Variance of Wages in the Presence of Selection and Unobserved Heterogeneity Stacey H Chen Stacey H Chen Search for other works by this author on: This Site Google Scholar Author and Article Information Stacey H Chen Online ISSN: 1530-9142 Print ISSN: 0034-6535 Copyright by the President and Fellows of Harvard College and the Massachusetts Institute of Technology2009 The Review of Economics and Statistics (2009) 91 (1): 227. https://doi.org/10.1162/rest.91.1.227 Connected Content This is a correction to: Estimating the Variance of Wages in the Presence of Selection and Unobserved Heterogeneity Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn Email Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation Stacey H Chen; Estimating the Variance of Wages in the Presence of Selection and Unobserved Heterogeneity. The Review of Economics and Statistics 2009; 91 (1): 227. doi: https://doi.org/10.1162/rest.91.1.227 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search View Original Article Copyright by the President and Fellows of Harvard College and the Massachusetts Institute of Technology2009 Article PDF first page preview Close Modal You do not currently have access to this content.